THE TRANSLATION METHOD OF PREPOSITION ON J.D SALINGER’S NOVEL OF THE CATCHER IN THE RYE TRANSLATED BY GITA WIDYA LAKSMINI - Lisa Nurhanifah; Dewi Kustanti; Nurholis Nurholis (Universitas Islam Negeri Sunan Gunung Djati, 2019)
This research tells about translation method of preposition. Preposition is the word that simple to translated, but it is complicate to find the good word, because there are so many meaning in dictionary. Even the translator does not always get the meaning from dictionary. This purpose of research is analyzing the translation of simple and complex preposition used in “J.D. Salinger’s Novel The Catcher in The Rye. And to find out the kinds of translation methods in translating of simple and complex preposition on it. The method of research uses descriptive qualitative method. Technique of collecting data, the researcher uses documentation. Technique of analyzing data, the researcher uses constant comparative method by Glaser and Strauss with four steps are data reduction, data categorization, data synthetization and hypothesis. The result of research is translator use four translation method of preposition. There are literal translation, semantic translation, free translation and communicative translation. mostly translator uses literal translation. Preposition has many meaning in dictionary, that’s why there are no word-for-word because researcher things that translator is process the translation of preposition. There are many kinds of preposition. The researcher dividing become two parts, are simple and complex (Randolph Quirk,1985). Simple preposition mostly available than complex in the novel. Because simple preposition is easy to find in the novel.Keywords: preposition, literal translation, semantic translation, free translation, communicative translation